Megaliths Discovered Around Neeloor, Kottayam District, Kerala: Some Observations - Ajit Kumar and N. Nihildas
Archaeological explorations conducted by the second author around Neeloor which lies 18 kilometer north of Pala have yielded six new megalithic sepulchral sites. The sites are in the localities of Mattathipara, Nerappu, Injukave, Kurumannu, Payazmound, and Vadakkummuri. Vadakkummuri is the only site which has yielded a dolmen and is in Todupuzha taluk of Idukki district. All other sites have yielded dolmenoid cists and are located in Meenachil taluk of Kottayam district. Some observations and discussions on the finds are annotated in this article